Adolescent Risk Substance Use Behavior, Posttraumatic Stress, Depression, and Resilience: Innovative Considerations for Disaster Recovery. Issue 3 (July 2021) - Fuchs, Robert; Glaude, Maurya; Hansel, Tonya; Osofsky, Joy; Osofsky, Howard
Natural and technological disasters cause long-term psychological trauma and increase substance use in adults. It is unclear whether these problems also occur in children and whether trauma influences long-term psychological outcomes due to developmental stages at the time of trauma. One community of interest is located in southeastern Louisiana, where, as children, many locals were exposed to Hurricane Katrina in 2005 and the Deepwater Horizon Oil Spill in 2010. We hypothesized individuals exposed to these disasters in early childhood would exhibit higher rates of anxiety, depression, and alcohol use as adolescents than the general population. To test this, we developed a questionnaire with a focus on severity of disaster exposure, indicators of psychological resilience, and current levels of anxiety, depression, and alcohol use. This survey was administered to over 1000 adolescents in local high schools throughout southeastern Louisiana. Structural equation modeling was performed to test correlations and moderation effects. We found disaster exposure was positively associated with trauma-like symptoms and substance use and psychological resilience was negatively related to these outcomes. These findings demonstrate childhood disaster exposure has the potential to cause chronic psychological distress and predispose individuals to substance use later in life. They also suggest resilience may be protective for disaster survivors. Future studies should expand these concepts to other age groups and types of disasters. Whether resilience-focused psychotherapy may be beneficial in these populations is also a relevant topic for exploration.